HUBUNGAN KEMATANGAN EMOSI DENGAN KONFORMITAS PADA REMAJA - Rachmawati, Fema (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstractThis study aimed to determine the relationship between the emotional maturity to conformity in adolescents. The subjects were students of class XI at SMA Muhammadiyah 3 Yogyakarta. Data collection methods used in this research is the scale, the scale of conformity and emotional maturity scale. Analysis using Pearson´s correlation technique of Product Moment and help computing statistical program SPSS for Windows 18:00. Categorization results showed 90 contained 73% of the study subjects had the emotional maturity of categorization was, 92 contained 74% of the study subjects had moderate conformity to the categorization. Based on the comparison of hypothetical Mean Mean empirical and emotional maturity categorization of subjects included in the study were likely to be high, whereas conformity categorization of subjects included in the study were likely to be high. The results of the correlation coefficient r = 0.278 with a significance level (p) 0.002 (p <0.01). The results showed that there is a significant positive relationship between the variables with the variables of emotional maturity on adolescent conformity. Based on the analysis we concluded that there is a significant positive relationship between the variables of emotional maturity on adolescent conformity with the variable, meaning that the higher the emotional maturity of higher conformity, conversely the lower the lower the emotional maturity of conformity.Keywords: Emotional maturity and conformity